Alterations in cytoskeletal proteins and microtubule stability following 26S proteasome dysfunction in mouse brain cortical neurons - Mohamed, Hala Alhadi Ali (2017)
The mechanisms involved in the cause and progression of chronic neurodegenerative diseases are still unclear. The ubiquitin proteasome system (UPS) plays an essential role in the maintenance of intracellular protein homeostasis by degrading unwanted proteins. The accumulation of ubiquitinated proteins is a hallmark of major neurodegenerative diseases, including Alzheimer’s and Parkinson’s diseases. In most cases, these diseases are also associated with changes in cytoskeletal proteins and microtubule stability. We previously reported decreased levels of microtubule destabilizing protein stathmin (STMN) following 26S proteasome dysfunction in mouse cortical neurons; associated with neurodegeneration and the formation of intraneuronal protein inclusions in surviving neurons. This suggested a role for the 26S proteasome in maintaining the neuronal cytoskeleton. This thesis investigates the levels and localisation of cytoskeletal proteins in mouse cortical neurons following 26S proteasome dysfunction (Psmc1fl/fl;CaMKIIα-Cre). This study provides new insights into the role of the UPS in maintain cytoskeletal proteins that may be important in neurodegenerative disease. We found an early increase in neurofilaments following 26S proteasome dysfunction; before obvious changes in microtubule stability. An increased free/polymerised tubulin ratio was evident at later stages indicative of microtubule instability in Psmc1fl/fl;CaMKIIα-Cre mice. In addition, we found decreased levels of microtubule proteins, microtubule-associated proteins and detyrosinated-tubulin; with increased tyrosinated-tubulin following 26S proteasome dysfunction. These changes are contrary to decreased STMN expression observed in Psmc1fl/fl;CaMKIIα-Cre mice. We suggest that decreasing STMN may be part of a negative feedback loop to stabilize MT following 26S proteasome dysfunction. STMN is known to be a downstream target of p53, p27 and the PI3K/Akt pathway. We found expression of p53 was increased in the cortex following 26S proteasome dysfunction, correlating with decreased phosphorylated-Akt expression at an early stage and may effect STMN expression. However, we did not observe any significant differences in pro- and anti-apoptotic proteins of the Bcl-2 family between control and Psmc1fl/fl;CaMKIIα-Cre mice, which may also by effected by p53 and phosphorylated-Akt. Immunohistochemical studies revealed changes in cortical neuron morphology accompanied 26S proteasome dysfunction. Cortical thickness was significantly decreased; associated with less neurons in the layers III and V. However, nuclear size of cortical neurons was increased, as well as the length and arborisation of their apical dendrites. Taken together, our novel data contributes to our understanding of molecular and cellular events underlying neurodegeneration and suggest that control of microtubule changes may help to slow or restore pathology of neurons.